Modeling and Analysis Technical Performance of BLDC Motor (Electric Motorcycle) - Muhammad Ikram, Mohd Rashid; Muhamad Azrin, Adnan (2017)
The project will discuss about the modeling of a direct drive BLDC Motor electric motorcycle drive system for technical performance evaluation, where the operating cycle profiles used are based on actual road tests. It will explain how the measurement data can be processed and coupled with the “usual” model of a direct-drive dc-drive system, thereby extending common modeling approaches. Then, the different riding profiles will analyze with the dyno meter test. The results both illustrate the ability of such low-cost drives to serve for commuting purposes with moderate driving styles and their limits to support rather sporty rides.